Effect of Acacia melanoxylon fibre morphology on papermaking potential - Anjos, O. (2013)
Submitted by Maria Eduarda Pereira Rodrigues (erodrigues@ipcb.pt) on 2013-07-17T16:52:53Z No. of bitstreams: 1 2011_AJ_64_Anjos.pdf: 879181 bytes, checksum: 00a9d6215f87e7a7fd17801780adea4c (MD5)